Physiotherapeutic approach in genito-pelvic pain/penetration disorder - Nunes, Ana Carla da Silva; Lemos, Carla Iasmin Lima; Araújo, Nazete dos Santos; Nunes, Erica Feio Carneiro; Rodrigues, Cibele Nazaré Câmara (Manual Therapy, Posturology & Rehabilitation Journal, 2019)
Background: Sexual dysfunctions constitute a public health problem that affects many women during all stages of life, being able to influence physical and mental health, interfering with quality of life. Physical therapy plays a fundamental role in addressing these dysfunctions, with simple and low cost resources, promoting significant results in these cases. Objective: To analyze the effectiveness of a physical therapy protocol on the sexual function of women with genital-pelvic pain/penetration disorder. Methods: Uncontrolled clinical trial, in which participated 15 women with a mean age of 28 ± 4.2 years, who had 16 physical therapy sessions twice a week. The pelvic physiotherapy protocol consisted of the application of electroanalgesia, perineal massage, kinesiotherapy and vaginal dilators. Sexual function was assessed by the Female Sexual Function Index (FSFI) and pain by the Visual Analog Scale (VAS). Results: Given the proposed treatment, the FSFI responded significantly (p=0.0003) with a median improvement that was 19.70 initially and increased to 28.40 later. The VAS also obtained significant improvement (p=0.0003), from the initial median of 8.00 to final 0.00. Conclusion: It is suggested that the physical therapy program has brought significant results in sexual function and pain in women with genital-pelvic pain/penetration disorder.